Respuesta del cultivo de maíz (Zea mays) amarillo duro, a dos prácticas de labranza, dos fuentes nitrogenadas y dos formas de aplicación del fertilizante Sector Ahuashiyacu - Murrieta Vela, Wilmer (2006)
The present thesis work has taken place in “Fundo Miraflores" fields, situated to 3,5 km from Tarapoto city, Ahuashiyacu area, Banda de Shilcayo district, National University of San Martin property, geographically located in the following coordinates: 76° 001 west longitude, 06° 001 south longitude and 315 mt. over the sea level , with the aim of evaluating the effects of two terming practices, two nitrogen sources and two application methods and finally to make the economic analysis to the best treatments. The output and complementary vegetative characteristics were evaluated using an estadistic design of blocks completely at random with a factor arrangement of 2x2x2 and thre repetitions the results were analyzed through the vary analysis and “Duncan" multiple signification test. The experimental ground was a sandy texture soil with add reaction (PH = 4.8) mid content of organic material (2.38 %), mid nitrogen content, low content of phosphorus, mid content of potassium, and a 73 % of aluminium saturation. The distance range of sowing, was 0.80 mt between rows and 0.50 mt between groups with a population density of 50 000 plants per hectare; for the farming practice a ploughing and horrowing were made in mechanical and traditional way, the fertilization process was divided into fwo times, at the moment of the first sow (50 % de nitrogen) and the second part at the beginning of flowering (50 % of nitrogen). Two nitrogen sources were used, the ammonium sulphate and urea, with a mid temperture abont 24.9 °C and a total precipitation (rain) of 505.10 mm during the vegetative period. From the results and according to the estadistic analysis, it can be said that grain. At 14 % of moisture this values were between 3 815 to 2 510 kg/ha concern to T1 and T5 treatments. According to the agronomical characteristics evaluated in this investigation cost /benefit, it was determinate that the T1 treatment (plough harrow, and urea nitrogen source applied to the soil) was one of the best practices because of the output potencial and its profitability, with rents equal to Si. 38.33 (nuevos soles) per production hectare.